Population genomics demystifies the defoliation phenotype in the plant pathogen Verticillium dahliae. Issue 2 (25th February 2019) - Zhang, Dan‐Dan; Wang, Jie; Wang, Dan; Kong, Zhi‐Qiang; Zhou, Lei; Zhang, Geng‐Yun; Gui, Yue‐Jing; Li, Jun‐Jiao; Huang, Jin‐Qun; Wang, Bao‐Li; Liu, Chun; Yin, Chun‐Mei; et al.
Summary: Verticillium dahliae is a broad host‐range pathogen that causes vascular wilts in plants. Interactions between three hosts and specific V. dahliae genotypes result in severe defoliation. The underlying mechanisms of defoliation are unresolved. Genome resequencing, gene deletion and complementation, gene expression analysis, sequence divergence, defoliating phenotype identification, virulence analysis, and quantification of V. dahliae secondary metabolites were performed. Population genomics previously revealed that G‐LSR2 was horizontally transferred from the fungus Fusarium oxysporum f. sp. vasinfectum to V. dahliae and is exclusively found in the genomes of defoliating (D) strains. Deletion of seven genes within G‐LSR2, designated as VdDf genes, produced the nondefoliation phenotype on cotton, olive, and okra but complementation of two genes restored the defoliation phenotype. Genes VdDf5 and VdDf6 associated with defoliation shared homology with polyketide synthases involved in secondary metabolism, whereas VdDf7 shared homology with proteins involved in the biosynthesis of N ‐lauroylethanolamine ( N ‐acylethanolamine (NAE) 12:0), a compound that induces defoliation. NAE overbiosynthesis by D strains also appears to disrupt NAE metabolism in cotton by inducing overexpression of fatty acid amide hydrolase. The VdDf s modulate the synthesis and overproduction of secondary metabolites, such as NAE 12:0, that cause defoliation either by altering abscisic acid sensitivity, hormone disruption, or sensitivity to the pathogen.